SARS-CoV-2 Infection and Associated Cardiovascular Manifestations and Complications in Children and Young Adults: A Scientific Statement From the American Heart Association. Issue 19 (11th April 2022) - Jone, Pei-Ni; John, Anitha; Oster, Matthew E.; Allen, Kiona; Tremoulet, Adrianna H.; Saarel, Elizabeth V.; Lambert, Linda M.; Miyamoto, Shelley D.; de Ferranti, Sarah D.
Abstract : Coronavirus disease 2019 (COVID-19) resulted in a global pandemic and has overwhelmed health care systems worldwide. In this scientific statement, we describe the epidemiology, pathophysiology, clinical presentations, treatment, and outcomes of severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) and multisystem inflammatory syndrome in children and young adults with a focus on cardiovascular manifestations and complications. We review current knowledge about the health consequences of this illness in children and young adults with congenital and acquired heart disease, the public health burden and health disparities of this infection in these populations, and vaccine-associated myocarditis.